PERLINDUNGAN HUKUM TERHADAP GURU DALAM PENYELENGGARA PENDIDIKAN BERDASARKAN UNDANG-UNDANG NO. 14 TAHUN 2005 TENTANG GURU DAN DOSEN - Umar Iskandar; A. Osfira Rosary (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Protect teacher/lecturer educators in carrying out their noble duties, the development of Indonesian national education gained new strength and enthusiasm with the enactment of Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. The ratification of Law of the Republic of Indonesia Number 20 of 2003 also has consequences or implementation for education, including that teachers and education staff have the right to obtain legal protection in carrying out their duties and rights to intellectual property results. The aim is to find out and analyze how legal protection is and what factors influence legal protection for teachers in education providers based on Law no. 14 of 2005 concerning Teachers and Lecturers. The research method used is a qualitative sociological juridical approach. The sociological juridical research used in this study was to see how the community's understanding of teacher protection. Therefore the sociological juridical approach has a very big role to see the community's understanding of teacher protection. The results of this study 1. The protection of teachers in carrying out their duties as educators has been regulated in Law Number 14 of 2005 concerning Teachers and Lecturers Regulation of the Minister of Education and Culture Number 10 of 2017 concerning Protection for Educators and Education Personnel. 2. The factors that affect the legal protection of teachers in the administration of education based on law no. 14 of 2005 About Teachers and Lecturers is a factor of legal culture, factors of the rule of law, and factors of legal structure.